2005
DOI: 10.1007/s00198-005-1955-8
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between periodontitis and loss of mandibular bone in relation to systemic bone changes in postmenopausal Japanese women

Abstract: A new method of measuring mandibular alveolar bone mineral density (BMD) was applied to 40 postmenopausal Japanese women aged 50-69 years exhibiting minimal to mild periodontal diseases. Lumbar spine BMD was measured by dual X-ray absorptiometry (DXA) and calcaneus speed of sound (SOS) by quantitative ultrasound (QUS). There were age-related decreases of alveolar BMD, calcaneus SOS and vertebral BMD. There were significant correlations between two of the respective bone mass values. Correlations between clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 10 publications
3
43
1
1
Order By: Relevance
“…22,23,29,30 The correlation between mandibular BMD and other skeletal sites assessed by various techniques have also been reported. 14,15,22,[31][32][33][34] Similarly, we found significant positive correlation between mandibular and femoral BMD. However, a recent study reported that the BMD of the jaw measured using DXA was not correlated with femoral BMD.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…22,23,29,30 The correlation between mandibular BMD and other skeletal sites assessed by various techniques have also been reported. 14,15,22,[31][32][33][34] Similarly, we found significant positive correlation between mandibular and femoral BMD. However, a recent study reported that the BMD of the jaw measured using DXA was not correlated with femoral BMD.…”
Section: Discussionsupporting
confidence: 77%
“…30 The association between systemic BMD and periodontal disease has been addressed in a number of studies. 6,[9][10][11][12][13][14][15][16][17][18][19][20] While the cross-sectional studies conducted on post-menopausal osteoporotic females and elderly males suggested that there was a correlation between systemic BMD and periodontal disease, [9][10][11]14,35 other studies conducted on pre-menopausal females and young male populations did not support such a relationship. 6,12,13 A recent longitudinal study conducted on elderly Chinese males suggested that osteoporosis is associated with severe loss of clinical attachment and interproximal gingival recession.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…11 risk groups, which may explain why conclusions on the relationship between osteoporosis and periodontitis are disputed [30][31][32][33][34]. The present study identified a strong relationship between the periodontitis and osteoporosis, and especially for the risk of a future fracture if the older person had a diagnosis of both osteoporosis and periodontitis.…”
Section: Accepted M Manuscriptmentioning
confidence: 65%